Impact of SO2 on the Oxygen Exchange Kinetics of the Promising SOFC/SOEC Air Electrode Material La0.8Ca0.2FeO3-δ. Issue 10 (1st June 2017) - Berger, Christian; Bucher, Edith; Gspan, Christian; Menzel, Alexander; Sitte, Werner
Abstract : The mass and charge transport properties of La0.8 Ca0.2 FeO3-δ (LCF82) were determined at 600–800°C and pO2 = 0.1 bar. The electronic conductivity is in the range of 112 S cm −1 at 700°C. The chemical surface exchange coefficient (kchem ) and the chemical diffusion coefficient of oxygen (Dchem ) were measured. LCF82 shows exceptionally fast oxygen exchange kinetics in pure O2 -Ar at 700°C. Long-term measurements at 700°C in pure O2 -Ar showed an excellent stability of the kinetic parameters during 1000 h. However, when 2 ppm of sulfur dioxide were added, kchem decreased by a factor of 40 within the first 24 h. After further 1000 h, the total decrease in kchem amounted to two orders of magnitude. Post-test analyses of LCF82 were performed by SEM-EDXS, XPS, and STEM. Ca-enrichment and La-/Fe-depletion of the LCF82 surface occurred during the first 1000 h without SO2 . At the surface of the sample exposed to 2 ppm SO2 for additional 1000 h, CaSO4 crystals with diameters of 1–2 μm and an underlying layer of Fe2 O3 (thickness approx. 300–450 nm) were found. Remarkably, LCF82 shows faster oxygen exchange kinetics than La0.6 Sr0.4 CoO3-δ even in the degraded state. Therefore, LCF82 is suggested as a promising material for SOFC and SOEC air electrodes.